Subjective time poverty: A gendered analysis - Pamella Spelman; Uma Kollamparambil (Economics and Econometrics Research Institute (EERI), 2024)
This study aimed to assess the extent and identify the socio-economic predictors of subjective time poverty across genders, using a general population sample in Gauteng province of South Africa. Based on the composite time poverty index, 22% of men and 16.7% of women report being time poor. The proportion of men who reported time poverty was significantly higher than that of women across all domains of time (general, family and leisure). This is a surprising finding considering that studies based on objective measures of time poverty have found women to experience higher time poverty due to their disproportionate share of unpaid domestic and caregiving responsibilities. The dissonance between objective and subjective measures of time poverty indicate that social context and individual perspectives contribute to the nuanced ways in which men and women assess their time and report feelings of time poverty. Further, the study identified both similarities and dissimilarities amongst predictors of subjective time poverty across genders. While age, residing in an informal dwelling and lengthier commute times had consistent association with time poverty across both genders and all three time domains, some other covariates (income, children, elderly, and employed) were found to have differences in the association with time poverty for male and female reinforcing the complex relationship between subjective time poverty and socioeconomic factors that is shaped by gendered norms and perceptions.
Keywords: E24; I32; J1; 330; subjective time-poverty; gendered analysis; ordinal regression; general timepoverty; family time-poverty; leisure time-poverty